2022
DOI: 10.3390/ijfs10030075
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Portfolios of National Currencies, Commodities and Fuel, Agricultural Commodities and Cryptocurrencies during the Russian-Ukrainian Conflict

Abstract: This study sets out to explore the impacts of the Russian-Ukrainian conflict on worldwide financial markets by considering a large array of national currencies, precious metals and fuel, agricultural commodities and cryptocurrencies. Estimations span the period since the Russian invasion until the takeover of the Ukrainian city of Mariupol. Optimal portfolios are constructed for separate categories of financial assets for different levels of risk-aversion by investors. The Chinese yuan, gold, corn, soybeans, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
(93 reference statements)
0
5
0
Order By: Relevance
“…They argue that BTC shows more vital connectedness to other markets over time, and it is heterogeneous in the direction of information spillovers from different segments of agricultural commodity markets. Kyriazis (2022) found evidence that a portfolio of agricultural commodities would perform best after the outbreak of the Russia-Ukraine war in 2022, while a portfolio containing cryptocurrencies would not be worth considering for its risk-reward.…”
Section: T Er At U R E R Ev I Ewmentioning
confidence: 99%
“…They argue that BTC shows more vital connectedness to other markets over time, and it is heterogeneous in the direction of information spillovers from different segments of agricultural commodity markets. Kyriazis (2022) found evidence that a portfolio of agricultural commodities would perform best after the outbreak of the Russia-Ukraine war in 2022, while a portfolio containing cryptocurrencies would not be worth considering for its risk-reward.…”
Section: T Er At U R E R Ev I Ewmentioning
confidence: 99%
“…Yang (2023) also found that the war negatively impacts the crypto market, evidenced by reduced trading volumes for Bitcoin. Bitcoin and Ethereum have offered profit opportunities for risk‐seeking investors, while the overall cryptocurrency portfolio has experienced a poor risk–return trade‐off (Kyriazis 2022). The cryptocurrency SOL was found to be less affected compared to BNB and XRP (Ma 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, Kyriazis noteed that the outbreak of the Russian-Ukrainian military conflict on February 24 had a considerable impact on the global financial markets. This event led to a rise in risk aversion in the financial markets, which resulted in a gradual rise in the price of US bonds [13].…”
Section: Us Treasuriesmentioning
confidence: 99%